# Correct the error in the statement (3) by rewriting it so it follows from statements (1) and (2). (1) If Janet finishes her homework, then she will watch...

Correct the error in the statement (3) by rewriting it so it follows from statements (1) and (2).

(1) If Janet finishes her homework, then she will watch TV.

(2) If Janet watches TV, then she will eat pretzels.

(3) If Janet ate pretzels, then she finished her homework.

### 1 Answer | Add Yours

(1) and (2) are If - then statements:

*p*: Janet finishes her homework

*q*: Janet watches TV

*r*: Janet eats pretzels

(1) If *p*, then *q. *Symbolically, `p->q`

(2) If q , then r. Symbolically, `q->r`

Combining (1) and (2), we get `p->q->r` , or `p->r` .

This transates to

**If Janet finishes her homework, she will eat pretzels.**

(In the given statement (3) consequent and antecedent are reversed.)